AutiSim: A virtual reality simulation game based on the autism spectrum disorder - Mustafa Albakri, Ikmal Faiq Albakri; Muhd Farid Arfian, Muhammad Aliff; Shahbodin, Faaizah; Mokhtar, Mohd Khalid; Abdullah, Asniyani Nur Haidar; Mohd Suaib, Norhaida; Nor'a, Muhammad Nur Affendy; Jahidin, Abdul Hasib (The Science And Information (SAI) Organization Limited, 2025)
Technologies with altering reality like virtual reality (VR) have become more relevant to the public for their capabilities in the entertainment and healthcare field, as well as affordable for everyone. However, the emphasis on mental health-related simulation is often ignored due to technical complexities and wrong representation. Therefore, this study leverages the immersive capabilities of VR to create an engaging and educational game experience that simulates the sensory and social challenges faced by individuals with autism spectrum disorder (ASD). The study involves designing and implementing a VR game that places users in various scenarios reflecting the daily experiences of autistic individuals. The VR game aims to educate players about common misconceptions, sensory sensitivities, and social difficulties associated with autism. A literature review on XR technology and ASD was conducted during the pre-production phase to explore past research on autism in video games and shape the overall game vision. The study continues with developing animmersive simulation game using VR with locomotive motion controls and an artificial intelligence non-playable character (AI NPC) with Speech-To-Text function. Finally, the testing phase used two approaches: quantitative analysis, using the System Usability Scale (SUS) to assess usability and the Simulator Sickness Questionnaire (SSQ) to identify discomfort issues such as headaches and blurriness during gameplay, and qualitative analysis, gathering expert’s feedback on the VR game's content and teaching effectiveness.